(untitled) (Global Journal of Human-Social Science, 2013)
This study examined the product of primary education as asset to societal development and a link to basic decision making. The subject (180) primary six pupils and 90 primary school teachers were drawn from the schools that were involved in the study. The study was a descriptive one in which the ex-post facto survey method was used. Thee different instruments were used. They are: English Language Achievement Test (ELAT), Primary Mathematics Achievement Test (PMAT) and the Teachers’ questionnaire. The results showed that the products of primary school education are useful to themselves and to the society at large (Chi squared calculated = 72.80, df = 2; p < 0.05). The study further established government intentions to make products of primary education functional and productive citizens/ members of the society (Chi squared calculated = 18.07, df = 2; p